Midwifery Care for Pregnant Women in the Third Trimester with Complaints of a Flat Stomach at the Clinic: Asuhan Kebidanan Pada Ibu Hamil Trimester III Dengan Keluhan Perut Kenceng-Kenceng di Klinik - Maulida, Medita Chaidar Zuhrotul; Machfudloh, Hanik; Kusumawardani, Paramitha Amelia (Universitas Muhammadiyah Sidoarjo, 2020)
Pregnancy is a condition in which there is an embryo or fetus in the womb of a woman. The gestation period starts from conception until the fetus is born. First Day of Last Menstruation is used to calculate the normal length of pregnancy which is 280 days (40 weeks or 9 months 7 days). Complaints of a tight stomach in third trimester pregnant women are the result of false contractions, fetal movement in the womb, and also because of digestive disorders. The case study method uses a descriptive method. The case study was carried out at BPM Ernyadi Krian Sidoarjo which began on December 20, 2019. Midwifery care was carried out through assessment and evaluation. Midwifery care carried out by the author went smoothly and without any complications. In the results obtained from data collection, there is no gap between reality and theory.